Distribution. E in Vespertilionidae - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
Distribution. E France to N Europe well above the Arctic Circle in Norway, Sweden, and Finland, Central Europe, Caucasus, NW Iran, and Central Asia (including N Kazakhstan) through Russia and N Mongolia to Russian Far East including Sakhalin I and Kamchatka Peninsula and S through Amur region into NC & NE China (Inner Mongolia [= Nei Mongol], Heilongjiang, Jilin, and Shandong) and Korean Peninsula, including Hokkaido and Okushirito inJapan and Kuril Is (Kunashir and Iturup); there are occasionally vagrant records throughout Europe as far S as Bulgaria and Italy and W into S Britain. Published as part of Don E. Wilson & Russell A. Mittermeier, 2019, Vespertilionidae, pp. 716-981 in Handbook of the Mammals of the World – Volume 9 Bats, Barcelona :Lynx Edicions on page 851, DOI: 10.5281/zenodo.6397752